Legislative program of the Socialist Party : record of the work of the socialist representatives in the state legislatures of the United States, 1899-1913 : with account of efforts of the Party in direct legislation - Mills, Ethelwyn (Chicago : Socialist Party, 1914)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Socialistische Partij; Verenigde Staten